Menanamkan Nilai-nilai Antikorupsi dan Menumbuhkan Kesadaran Etika di SMA Negeri 55 Jakarta - Santi Rimadias; Vidiyanna Rizal Putri; Javine Hagin Maengga; Habibi Mustofa; Muhammad Fikri Azmi; Muhammad Irfan Fadhilah Daulay; Yunda Satria Putrandally; Indra Satria Utama (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Corruption is still a big challenge in Indonesia, so it requires the introduction of anti-corruption education from an early age. The community service team from STIE Indonesia Banking School initiated a comprehensive outreach program at SMA Negeri 55 Jakarta which aims to instill anti-corruption values ​​and foster ethical awareness among students. The program uses a combination of lectures and interactive discussions, involving not only students but also teachers and school staff. The results show increased knowledge that students, through active participation in extracurricular activities, classroom learning, and daily social interactions, play an important role in developing anti-corruption character and ethical awareness. In addition, teachers and school staff play an important role in modeling and reinforcing the principles of integrity, responsibility, and honesty, thereby guiding students in embracing these core values. This initiative highlights the collective efforts required to foster a culture of integrity in educational settings.